Predictive approach to thermodynamic properties of Co nitrides and phase stability in the Co-N system - Fernández Guillermet, Armando; Jonsson, Stefan (Comisión Nacional de Energía Atómica; Argentina)
Fil: Fernández Guillermet, Armando. Comisión Nacional de Energía Atómica; Argentina